FENOMENOLOGI PENGALAMAN GURU DALAM MENGIMPLEMENTASIKAN KURIKULUM MERDEKA DI SMAN 2 SUTERA - Sefrinal Sefrinal; Zelhendri Zen; Jasrial Jasrial; Revi Handayani; Filma Alia Sari (Jurnal Manajemen Pendidikan, 2025)
This study aims to understand teachers’ experiences in implementing the Merdeka Curriculum at SMAN 2 Sutera through a phenomenological educational approach. The research focuses on the meaning of teachers’ lived experiences in responding to the paradigm shift from content-based instruction to the reinforcement of 21st-century competencies. Data were collected through in-depth interviews, classroom observations, and documentation involving eight teachers from various subject areas. Data analysis followed the stages of phenomenological reduction, essential meaning construction, and thematic interpretation. The findings reveal that the implementation of the Merdeka Curriculum at SMAN 2 Sutera is characterized by pedagogical adaptation dynamics, limitations in digital resources, and teachers’ reflective awareness of students’ learning autonomy. These findings highlight the importance of continuous professional development through contextual training and teacher learning communities to realize meaningful and independent learning.